Análisis e interpretación de los estados financieros de la Cooperativa de Ahorro y Crédito de la pequeña empresa CACPE-Celica, periodo 2012 - 2013 - Jumbo Armijos, Margarita de Jesús (2015)
The implementation process begins with the collection of basic information such as the production of the financial statements of the cooperative, legallysigned andauthenticated by the respective manager andaccountant; then proceed to implement each of the techniques of financial analysis and vertical analysis is to determine there presentativenessandeach account with the group to which it belongs; horizontal analysisto determinethe causes ofvariations inthe accounts ofa periodwithrespect to each otherand ownfinancial indicatorsfor this type oflending organizations. The main conclusions that can manifest cooperative techniquerequires financial analysis as a means to study the behavior of its financial statements at any given moment and make recommendations based primarily on objective data with their cooperative reality. From the results, it can be considered that the cooperative hasa favorable caught within the city dueto their services andofferedfinancialproducts,whichhas earnedthe confidenceof saversaccounttosee thisinstitutionan opportunity to improvesubstantiallytheir living conditions